MY SAY: The making of ‘bottom millionaires’ - Abd Razak, Dzulkifli (2009)
The alleviation of poverty has always been an important part of the socioeconomic agenda. At the global level, for example, the UN aims to reduce the number of the poor to half by 2015, as set out in its Millennium Development Goals blueprint. The eradication of extreme poverty was one of the eight goals the UN adopted at a summit of 189 nations in 2000. Numerous attempts have been made to turn this vision into reality. When Paul Collier wrote The Bottom Billion (2007), he asked: "Why are the poorest countries failing and what can be done about it?" In his book, he tells you why impoverished countries have failed to progress despite international aid and support. He makes reference to about 60 economies where almost one billion people live in what he calls "trapped countries". Their average life expectancy is said to be just 50 years and about one in seven children is expected to die before the age of five.